Problems of Oral Anticoagulation in an Adult with Homozygous Protein C Deficiency and Late Onset of Thrombosis - Pescatore, P; Horellou, H M; Conard, J; Piffoux, M; Van Dreden, P; Ruskone-Fourmestraux, A; Samama, M (Thrombosis and Haemostasis, 1993)
We describe a 57-year-old woman with homozygous protein C deficiency and mild thrombotic manifestations consisting of three spontaneous distal deep vein thromboses occurring after the age of 45. Previous surgery and pregnancies had been uneventful. Low but detectable protein C antigen and activity levels (both 20%) were discovered on the occasion of skin necrosis induced by oral anticoagulation. This therapy was interrupted because of skin necrosis and several episodes of disseminated intravascular coagulation (DIC) at the initiation of treatment despite a cautious protocol. No recurrent thromboembolic event has occurred in our patient using prophylactic doses of low molecular weight heparin for 24 months. New therapeutic approaches might be the administration of low molecular weight heparin or oral anticoagulation associated with protein C replacement in the induction period. This case reflects the variability of expression of protein C deficiency as well as the potential hazards of antivitamin K anticoagulation in this disorder.